2022
DOI: 10.1177/00222437221118856
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Efficacy of Time Scarcity Marketing Promotions in Online Retail

Abstract: Time scarcity promotions (e.g., “40% off for a limited time”) are mainstays of retail marketing. But might translating them to online shopping contexts alter or nullify their efficacy? The authors first report a meta-analysis of published and unpublished research as well as a simulated shopping experiment suggesting that the positive effects of time scarcity promotions observed offline may not emerge in online shopping contexts. They then posit that this difference arises because, in the online context, time s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…However, whether this is the case is far from a foregone conclusion; previous research on the effects of a related restriction (i.e., limitation of the time people have to process stimuli) has produced mixed results: whereas some work has found that people cope with time pressure by allocating additional cognitive resources and adopting more efficient processing strategies (Donkin, Little, and Houpt 2014; Payne, Bettman, and Johnson 1993; Pieters and Warlop 1999), other studies have suggested that it might interrupt processing (De Dreu 2003; Svenson and Maule 1993) by adding emotional, psychological, and physiological stress-related costs to already cognitively demanding tasks (Eysenck et al 2007; Margittai et al 2016; Sanbonmatsu and Kardes 1988). Similarly, although some research has shown that limiting the time consumers have to make a purchase (i.e., an “exploding offer”) increases sales (Aggarwal and Vaidyanathan 2003), other work has argued that such tactics can backfire (Hmurovic, Goldsmith, and Lamberton 2016) or simply have no observable effect (Hmurovic, Lamberton, and Goldsmith 2022).…”
Section: The Psychology Of Ephemeralitymentioning
confidence: 99%
“…However, whether this is the case is far from a foregone conclusion; previous research on the effects of a related restriction (i.e., limitation of the time people have to process stimuli) has produced mixed results: whereas some work has found that people cope with time pressure by allocating additional cognitive resources and adopting more efficient processing strategies (Donkin, Little, and Houpt 2014; Payne, Bettman, and Johnson 1993; Pieters and Warlop 1999), other studies have suggested that it might interrupt processing (De Dreu 2003; Svenson and Maule 1993) by adding emotional, psychological, and physiological stress-related costs to already cognitively demanding tasks (Eysenck et al 2007; Margittai et al 2016; Sanbonmatsu and Kardes 1988). Similarly, although some research has shown that limiting the time consumers have to make a purchase (i.e., an “exploding offer”) increases sales (Aggarwal and Vaidyanathan 2003), other work has argued that such tactics can backfire (Hmurovic, Goldsmith, and Lamberton 2016) or simply have no observable effect (Hmurovic, Lamberton, and Goldsmith 2022).…”
Section: The Psychology Of Ephemeralitymentioning
confidence: 99%
“…We used Facebook Ads Manager's split-testing function (Orazi and Johnston 2020) to test the effectiveness of different ad messages. Facebook advertising is commonly used by organizations to promote health behaviors (e.g., vaccinations; Hunt et al 2022) and is increasingly used by academic marketing researchers (e.g., D’Angelo and Valsesia 2022; Hmurovic, Lamberton, and Goldsmith 2022). Following these researchers, we use click-through rate (CTR; total number of clicks divided by total number of impressions) as our dependent variable.…”
Section: Studies 6a and 6b: Uptrend Messaging Versus Extant Approachesmentioning
confidence: 99%
“…Scarcity promotions (e.g., limited-time, limited-quantity) have been shown to be powerful drivers of purchase behavior (see Hmurovic, et al, 2023 for review). However, the shopping contexts in which scarcity promotions are used have evolved since most of the seminal work on such promotions was conducted.…”
Section: Promotionmentioning
confidence: 99%
“…However, the shopping contexts in which scarcity promotions are used have evolved since most of the seminal work on such promotions was conducted. For instance, recent work has shown that time scarcity promotions (e.g., countdown timers) have become much less effective online (vs. offline; Hmurovic, et al, 2023 ), partly due to their proliferation in online shopping environments, which has made consumers wearier of them in that context. In a similar vein, the product shortages and quantity restrictions experienced throughout the COVID-19 pandemic may have impacted how consumers now respond to limited-quantity promotions.…”
Section: Promotionmentioning
confidence: 99%